Alcohol Accessibility and Family Violence-related Ambulance Attendances - Scott, Debbie (Journal of interpersonal violence, 2022)
There is substantial evidence supporting the association between alcohol license density and violent crime. However, the impact of different types of alcohol licenses on intimate partner and family violence is sparse. We explored the associations between access to alcohol outlets, and family and intimate partner violence using paramedic clinical records, given this service is often the first to respond to acute crises. Coded ambulance attendance data from 694 postcodes in Victoria, Australia, from July 1, 2016 to June 30, 2018 where alcohol or another drug, mental health or self-harm associated with family or intimate partner violence was indicated were examined. A hybrid model of spatial autoregressive and negative binomial zero-inflated Poisson-based count regression models was used to examine associations with alcohol outlet density and socioeconomic factors. We found that access to a liquor license outlet was significantly associated with family violence-related attendances across all types of outlets, including on-premise (late night) licenses (? = 1.73, SE: 0.18), restaurant licenses (? = 0.83, SE: 0.28), and packaged liquor licenses (? = 0.62, SE: 0.06). Our results demonstrate a significant relationship between alcohol-related harms in the context of family violence and provides evidence of the relationship between alcohol-related family violence in both victims and perpetrators. The findings of this study highlight the need for public health interventions such as licensing policy and town planning changes to reduce these harms by restricting alcohol availability.